Propofol attenuates high glucose-induced P66shc expression in human umbilical vein endothelial cells through Sirt1. (27th December 2018) - Wang, Jing; Qi, Jie; Wu, Qichao; Jiang, Hui; Yin, Yuehao; Huan, Yan; Zhao, Yanjun; Zhu, Minmin
Abstract: Perioperative hyperglycemia is a common metabolic disorder in clinic settings. Hyperglycemia leads to endothelial inflammation, endothelial cell apoptosis, and dysfunction, thus resulting in endothelial injury. Propofol (2, 6-diisopropylphenol) is a widely used intravenous anesthetic in clinic settings. Our previous study indicated that propofol inhibits mitochondrial reactive oxygen species (ROS) production via down-regulation of phosphatase A2 (PP2A) expression, inhibition of Ser36-p66shc dephosphorylation and mitochondrial translocation, thus improving high glucose-induced endothelial injury. The expression of p66shc was inhibited by propofol in hyperglycemic human umbilical vein endothelial cells (HUVECs). However, the mechanism by which propofol inhibits p66shc expression in hyperglycemic HUVECs is still obscure. In the present study, we mainly examined how propofol inhibited high glucose-induced p66shc expression in HUVECs. Compared with 5 mM glucose treatment, high glucose increased p66shc expression and decreased sirt1 expression, which was inhibited by propofol treatment. Moreover, EX527 (a sirt1 inhibitor) reversed the effect of propofol against high glucose-induced p66shc expression. However, EX527 did not reverse the effects of propofol against high glucose-induced ROS accumulation, endothelial inflammation, and apoptosis. Furthermore, when cells were incubated with propofol, EX527, and FTY720 (a PP2A activator) simultaneously, the effects of propofol against high glucose-induced ROS accumulation, inflammation, and apoptosis were reversed. Our results suggested that propofol inhibited high glucose-induced p66shc expression via upregulation of sirt1 expression in hyperglycemic HUVECs. Moreover, propofol protects against high glucose-mediated ROS accumulation and endothelial injury via both inhibition of p66shc expression and dephosphorylation of Ser36-p66shc.